Design and Implementation of Intelligent Interoperability Framework for Heterogeneous Subsystems in Smart Home Environment - Perumal, Thinagaran (2011)
Recent advances in computing and communication technologies paved the growth for applications and heterogeneous subsystems in smart home environment. A typical smart home is highly characterized by heterogeneity subsystems that need to perform joint execution of operation in an efficient manner. Significant growths of subsystems are visible especially with new services, applications and devices in smart home environment. Nevertheless the need for interoperability elements still seems elusive. In general, these subsystems are isolated and consist of different operating system and tier of services. Current implementation of interoperability in smart home is in the form of dry-contact, lacking of intelligent mechanism that solves dependencies of heterogeneous subsystems in performing their operation respectively. There is significant need for a cross-platform interoperability solution that could make the subsystems ‘talk’ each other and operate in an interoperable manner within smart home environment. This brings forth the debate of choosing Web Services technology as premier interoperability platform. Being a distributed architecture, smart home environment requires certain degree of interoperability to manage subsystems comprising of different platforms. Web Services seems to be the emerging technology that could lead the way in providing greater interoperability. In this thesis, an intelligent interoperability framework is designed and implemented for managing heterogeneous subsystems in smart home environment. By inheriting the capabilities of XML SOAP technology and Web Services, three new algorithms based on Event-Condition-Action (ECA) paradigm have been developed to facilitate efficient interoperation of the heterogeneous subsystems. The first algorithm, named as Framework Initialization algorithm, is developed to initialize the framework and discovering the subsystems configured in order to derive the interoperation tasks. The second algorithm, named as Asynchronous Event-Driven algorithm is derived to manage heterogeneous subsystems in smart home environment. Besides, this algorithm provides home users or application developers to implement their own event operators with bespoke syntax for their application purpose by defining cross-events corresponding to the event operators. The third algorithm, named as Pro-Active Intelligence algorithm has inspired autonomous action triggering for each event interoperation, using a control action statement that is generated by SOAP packets required for joint execution of tasks among heterogeneous subsystems. A Home Application Server (HAS) was configured for proof of concept. The framework implementation has been tested to clarify its outstanding advantages over the conventional interoperability solution as well as the performance of message transactions for events in smart home environment corresponding with response time, heterogeneous ECA interoperation, and conformance reliability. Based on the response time result without load, it is evident that the average time utilization for single operation of subsystem is 25.87ms, validates the smart home requirement. For ECA interoperation test result, it is concluded that there are two significant performance drops with one at 10% and the other one at 30% of network load. The framework conformance testing also clearly stated that the stability range of the framework is visible from No Load till 50% load percentages. As a conclusion, this research contributes to the aspect of solving interoperability requirement for smart home environment in a federated manner.